2020
DOI: 10.1177/0024363920926018
|View full text |Cite
|
Sign up to set email alerts
|

Does the Uniform Determination of Death Act Need to Be Revised?

Abstract: Prompted by concerns raised by the rise in litigations, which challenge the legal status of brain death (BD), Lewis and colleagues recently proposed a revision of the Uniform Determination of Death Act (UDDA). The revision consists of (i) narrowing down the definition of BD to the loss of specific brain functions, namely those functions that can be assessed on bedside neurological examination; (ii) requiring that the determination of BD must be in accordance with the specific guidelines designated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Whether these criteria in fact succeed in demonstrating whole-brain death per UDDA, or even true brainstem death, is a matter of scientific and legal debate. 21 Although there is a definite lack of understanding for the scientific reasoning behind the AAN procedural criteria even on the part of MDs, at baseline there is a high degree of trust across training types that these criteria demonstrate loss of brain function that is irreversible. Even prior to the educational intervention that reviews scientific criticisms, there is remarkably less agreement, especially among MDs, that the AAN criteria determine complete loss of brain function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether these criteria in fact succeed in demonstrating whole-brain death per UDDA, or even true brainstem death, is a matter of scientific and legal debate. 21 Although there is a definite lack of understanding for the scientific reasoning behind the AAN procedural criteria even on the part of MDs, at baseline there is a high degree of trust across training types that these criteria demonstrate loss of brain function that is irreversible. Even prior to the educational intervention that reviews scientific criticisms, there is remarkably less agreement, especially among MDs, that the AAN criteria determine complete loss of brain function.…”
Section: Discussionmentioning
confidence: 99%
“…20 On the other hand, critics urge caution and reconsideration of the current criteria and its underlying rationale, since erroneous declaration of death in medical practice has catastrophic consequences on patients and families. 21,22 This academic controversy is reflected in clinical practice. It is relatively common for neurologists to encounter families who object to discontinuation of organ support after brain death 23 and yet survey studies have shown that neurologists do not have a consistent rationale for accepting brain death as death, nor a clear understanding of diagnostic tests for brain death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis and colleagues [34] propose that the defi nition of standing legal requirement of consent for testing [36,37]. While agreeing that the UDDA needs revision, Nguyen [35] maintains that the suggestions of Lewis and colleagues neither address the root cause of the litigations (harm caused by testing) nor the controversies about the neurological declaration of brain death.…”
Section: Proposals For Legislative Reformmentioning
confidence: 99%
“…Several of the observers have independently submitted their opinions on how the committee should rewrite the UDDA for publication in Neurology 22 and other journals. [23][24][25] To explain the context and content of these issues for practicing neurologists, Neurology Editor, José Merino commissioned a series of articles on the UDDA and brain death of which this is the first. Here I outline the history and critiques of the UDDA and try impartially to provide the context for the debates over how it should be revised.…”
mentioning
confidence: 99%